2018
DOI: 10.1080/00071668.2018.1440378
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a meal feeding regimen and the availability of fresh alfalfa on growth performance and meat and bone quality of broiler genotypes

Abstract: 1. The aim of this study was to identify a feeding regimen that encourages good pasture use in slow (SG) and fast (FG) growing broiler genotypes under free-range management. 2. SG and FG birds fed on either an ad libitum (ADB) or a meal feeding (MEF) programme were given free outdoor access with or without fresh alfalfa from day 22 to 72 and from day 22 to 45, respectively. In two consecutive trials, 800 birds of each genotype were included in a factorial design using groups of 40 birds replicated 5 times. 3. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Alfalfa quality determined mainly by protein content and fiber composition affects the digestibility and nutrition intake for animal feeding. Improving alfalfa quality by increasing crude protein or reducing fiber content has benefited animal husbandry (Koçer et al, 2018). Using QTL mapping combined with high throughput genotyping technology, we identified 83 regions associated with crude protein, fiber or lignin based on the phenotypic data of an F 1 population established by crossing two alfalfa parents with significant difference in quality.…”
Section: Discussionmentioning
confidence: 99%
“…Alfalfa quality determined mainly by protein content and fiber composition affects the digestibility and nutrition intake for animal feeding. Improving alfalfa quality by increasing crude protein or reducing fiber content has benefited animal husbandry (Koçer et al, 2018). Using QTL mapping combined with high throughput genotyping technology, we identified 83 regions associated with crude protein, fiber or lignin based on the phenotypic data of an F 1 population established by crossing two alfalfa parents with significant difference in quality.…”
Section: Discussionmentioning
confidence: 99%
“…in any of the measured WHC parameters between fast growing (Ross-308) and slow growing broilers (T2-Y2), while Kocer et al (2018) found higher drip-and cooking loss in fast growing broilers (Ross308) compared to slow growing (Hubbard Red-JA87). However, the housing conditions and the feeding regimens were different in these two trials.…”
Section: Discussionmentioning
confidence: 83%
“…However, the housing conditions and the feeding regimens were different in these two trials. Broilers with outdoor access (Kocer et al, 2018) showed higher WHC values in general compared to the broilers with only indoor access (Dogan et al, 2019). In our study, no difference related to outdoor access was found.…”
Section: Discussionmentioning
confidence: 99%
“…The values of crude protein, crude fiber, crude cellulose, and metabolizable energy contained in alfalfa are 17.5%, 24.1%, 20%, and 1200 kcal/kg, respectively [14,15]. Little is known about the effects of fresh forage consumption by poultry [16]. For instance, Suwignyo et al [17] reported that fresh alfalfa supplementation in ducks affected feed intake, body weight gain, and feed conversion ratio.…”
Section: Introductionmentioning
confidence: 99%